The Influence of the Experiential Marketing Approach on the Decision to Use Products and Services in Bank Syariah Indonesia (BSI) Customers, Abdullah Silondae 2 Branch Office, Kendari City - Mahfudz; Nurfadli, Aldiyansyah; Akmal (International Journal of Management Progress, 2023)
Experiential marketing is a marketing method that is driven by experience. Many studies have been conducted on this subject, but among the various studies on experiential marketing, there has been no research that specifically addresses experiential marketing on the decision to use products and services in banking. This study aims to see and test the effect of the Experiential Marketing Approach on Decisions to Use Products and Services at Indonesian Sharia Bank Customers at the Abdullah Silondae Branch Office 2. The type of data this study uses is a type of research with quantitative methods. Meanwhile, based on the type of data collection, this research uses a survey research type. Survey research is directed to find out and study data from samples taken from the population, so that relative events, distribution, and relationships between variables can be found. This research uses quantitative methods. Samples were obtained by 96 respondents by taking samples using purposive sampling technique. Meanwhile, the data collection technique was carried out using a questionnaire method and library research. Data is processed using Microsoft Excel and SmartPLS 4.0 software. From the results of data processing, it shows that the Experiential Marketing variable has a positive and significant effect on the Decision variable on the use of products and services at BSI.